Does household engagement in concurrent business affect the farm size-technical efficiency relationship in grain production?: Evidence from Northern China. Issue 1 (4th February 2019) - Zhong, Min; Zhu, Yuchun; Chen, Qihui; Liu, Tianjun; Cai, Qihua
Abstract : Purpose: The purpose of this paper is to examine how households' engagement in concurrent business (CB), which is measured by the contribution of off-farm income to household income, affects the farm size–technical efficiency (TE) relationship in Northern China. Design/methodology/approach: This paper applies a stochastic frontier analysis method to analyze data on 1, 006 rural households collected from four major wheat-producing provinces in Northern China, adopting a translog specification for the underlying production function. Findings: The analysis yields three findings. First, the farm size–TE relationship is inverted U-shaped for all CB engagement levels higher than 5 percent, and the most technically efficient farm size increases with the level of household CB engagement. Second, how TE varies with the level of CB engagement depends on farm size: an inverted-U relationship for relatively small farms (<10 μ ), a positive relationship for middle-size farms (10–20 μ ), and a negative relationship for large farms (>20 μ ). Finally, the overall TE score, 0.88, suggests that wheat output can be increased by 12 percent in Northern China if technical inefficiency were eliminated. Originality/value: Unlike most previous studies that examine the impacts of farm size and households' off-farm business involvement separately, this paper examines how these two factors interact with each other.